H∞ Observer Design for Linear Time-Delay Systems - Haq, Md Aminul; Kucukdemiral, Ibrahim Beklan (IEEE, 2015)
The paper present the design of an observer for a general class of systems with delays in states. A state space model of observer with delays is proposed. The novelty of the study is to include the state derivatives in the design. The stability of the observer is proved by Lyapunov approach. Linear Matrix Inequality (LMI) approach is used in the analysis of the problem. Numerical examples are studied to see the validity of the approach.
Keywords: STABILITY ANALYSIS; Engineering